Long-term growth response to weed-control strips in Eucalyptus urograndis plantations in Brazil - Tiburcio, R. A.S. (2023)
Several studies have reported the effect of weed competition on eucalypt plantations, but most have focused on initial growth. The aim of the study reported here was to evaluate the long-term growth response of Eucalyptus urograndis in weed-control strips of different widths and its competitive performance in a rotation area over seven years. An experiment was conducted in a commercial area (12 960 m2) in Eunápolis, Bahia, Brazil. The treatments consisted of weed-control strips with the following widths on both sides of eucalypt planting lines maintained for the first six months of crop cultivation: 0 cm (weedy check control); 25 cm; 50 cm; 75 cm; 100 cm; 125 cm; 150 cm; 175 cm; and 200 cm (weed-free control). The 125-cm weed-control strip obtained the best eucalypt growth performance after seven years, with a gain of 61.8% compared with the weedy check control. The competitiveness index of E. urograndis tended to increase after the first two years of cultivation, the period in which the interference caused by weeds was most accentuated.